Composite seed crystal for recovering lead ions in wastewater, preparation method and nucleation granulation salt separation process
By preparing a dedicated composite crystal species in lead -layer load -shaped dual -hydroxide surface load layer of the surface of the lead aluminum -shaped dual -metallic hydroxide surface, solve the problem of selective recycling difficulties in lead ionic recycling in the new energy battery wastewater, and achieve high purity and highness. Millet production of density.
Patent Information
- Application Number
- CN202411536789.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The prior art is difficult to achieve selective recycling of lead ions in new energy battery wastewater, resulting in low purity of granular bodies and low recycling efficiency.
The lead -aluminum -like dual -metal hydroxide is used as a substrate material. By serializing molybdenum sulfide on its surface, the dedicated composite crystal species are prepared to enhance the selective capture and enrichment of lead ions.
It significantly enhances the purity and density of the granular body, reduces the moisture content of the granularity, and makes it suitable for directly putting it into industrial production.
Smart Images

Figure CN119349748A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of wastewater treatment, and in particular to a composite crystal seed for recovering lead ions in wastewater, a preparation method and a nuclear crystal granulation and salt separation process. Background Art
[0002] The research and development and application of new energy batteries have promoted social energy transformation, reduced dependence on traditional fossil energy, reduced carbon emissions, and promoted the use of renewable energy; however, the mass production of new energy batteries has led to the generation of a large amount of wastewater containing precious metal ions. The discharge of wastewater will not only cause the loss of precious metal resources, but also cause serious pollution to the environment. Therefore, the recycling and comprehensive utilization of precious metal resources in new energy battery wastewater has important economic and environmental benefits.
[0003] For the treatment of new energy battery wastewater, the commonly used process treatment methods are chemical precipitation, electrolysis and ion exchange. The electrolysis method uses direct current to carry out redox reactions. By controlling the electrode potential, a single metal with relatively high purity can be obtained. It is suitable for treating high-concentration wastewater and wastewater with good diversion, but its energy consumption is large, the operating cost is high, and the heavy metal concentration in the wastewater must be greater than 2-3g / L to achieve a high current efficiency. It is not suitable for treating low-concentration wastewater; the ion exchange method can enrich and concentrate trace heavy metal ions in the wastewater, making the regeneration liquid easy to recover, but the capacity of the ion exchange agent is limited, and chemical agents need to be used during the regeneration process, which is easy to cause secondary pollution of the water body; the advantage of the chemical precipitation method is that the process is simple and the water treatment volume is large, but its treatment accuracy is limited. It often needs to be coupled with the ion exchange resin process for terminal precision treatment to ensure that the effluent meets the discharge standards. In addition, the large amount of high-water content sludge generated by the chemical precipitation method needs to be further treated, resulting in a lengthy process, a large footprint, and high treatment costs. In addition, the method has a weak selective recovery ability for precious metal ions in new energy battery wastewater.
[0004] In recent years, more and more research has been conducted on the nuclear crystal granulation and salt separation technology for the recovery of heavy metal ions in wastewater, and certain results have been achieved. Nuclear crystal granulation and salt separation technology can not only avoid the generation of sludge, but also reduce the recovery cost of heavy metal ions. However, for wastewater containing multiple metal ions, such as new energy battery wastewater containing cobalt ions, lead ions, zinc ions, nickel ions, etc., the use of conventional commercial crystal seeds such as quartz sand, garnet, coal gangue, hematite and fluorite can only remove the above-mentioned multiple metal ions simultaneously, and cannot achieve selective recovery of lead ions, resulting in the final granulation body with low purity, thereby reducing the recovery efficiency.
[0005] Therefore, how to provide a special seed crystal that can selectively and efficiently recover lead ions in wastewater, thereby improving the purity of the resulting granules and increasing economic benefits has become a problem that needs to be solved urgently. Summary of the invention
[0006] In order to solve the above technical problems, the present disclosure provides a composite crystal seed for recovering lead ions in wastewater, a preparation method and a nuclear crystal granulation and salt separation process. The composite crystal seed uses lead-aluminum layered double metal hydroxide as a matrix material, and a lead-specific composite crystal seed is obtained by loading layered molybdenum disulfide on the surface. The composite crystal seed enhances the selective capture / enrichment capability of lead ions in new energy battery wastewater, significantly improves the purity and density of the granulation body, and the obtained granulation body has a low moisture content and can be directly put into industrial production.
[0007] In a first aspect, the present disclosure provides a composite seed crystal for recovering lead ions in wastewater, wherein the composite seed crystal comprises a lead-aluminum layered double hydroxide and a layered molybdenum disulfide supported on the surface of the lead-aluminum layered double hydroxide.
[0008] In the present disclosure, a lead-aluminum layered double metal hydroxide is used as a matrix material, and its crystal structure is similar to that of a lead ion precipitate (obtained by the reaction of lead ions in lead-containing wastewater with a precipitant), which can effectively reduce the nucleation barrier of lead ions precipitated on the surface of the seed crystal, and strengthen the selective attachment precipitation of lead ions; and, by loading layered molybdenum disulfide on the surface of the matrix material, the selective enrichment ability of lead ions is further enhanced, and each layer of the layered molybdenum disulfide is composed of a layer of molybdenum atoms and two layers of sulfur atoms, and each sulfur atom forms a hexagonal ring structure around a central molybdenum atom, wherein the molybdenum atom is generally Mo 4+ The sulfur atoms mainly exist in the form of S 2- exists in the form of S 2- It has a strong bonding energy with lead ions and tends to form a stable Pb-S bond, thereby fixing the lead ions on the surface of the material and realizing the selective capture of lead ions in a multi-ion coexistence system.
[0009] The following are preferred technical solutions of the present disclosure, but are not intended to be limitations of the technical solutions provided by the present disclosure. Through the following technical solutions, the technical objectives and beneficial effects of the present disclosure can be better achieved and realized.
[0010] As a preferred technical solution of the present invention, in the composite seed crystal, the mass ratio of the lead aluminum layered double hydroxide to the layered molybdenum disulfide is 1:(0.15-0.6), for example, 1:0.15, 1:0.20, 1:0.25, 1:0.30, 1:0.35, 1:0.40, 1:0.45, 1:0.50, 1:0.55 or 1:0.60, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0011] In the present disclosure, the appropriate loading amount of layered molybdenum disulfide can play a synergistic role with the lead-aluminum layered double hydroxide matrix material to enhance the capture effect of lead ions. If the loading amount of layered molybdenum disulfide is too much, it will lead to excessive adsorption. Since the lattice structure of molybdenum disulfide and the product to be precipitated is inconsistent, lead ions cannot nucleate and grow on the surface of molybdenum disulfide, and the formed crystalline product cannot grow into a dense spherical granulation body, so that the solid-liquid separation efficiency cannot be enhanced.
[0012] As a preferred technical solution of the present invention, in the lead-aluminum layered double hydroxide, the molar ratio of lead to aluminum is (4-8):(1.5-5), for example, 4:1.5, 4:5, 5:5, 7:4, 8:4 or 8:5, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0013] In the present disclosure, appropriate lead and aluminum elements are beneficial to enhancing the ability to capture lead ions; whether it is too much lead or too much aluminum, it will lead to the collapse of the layered structure, resulting in a decrease in the specific surface area of the material and a weakening of the ability to capture lead ions.
[0014] In a second aspect, the present disclosure provides a method for preparing the composite seed crystal according to the first aspect, the preparation method comprising the following steps:
[0015] Lead-aluminum layered double hydroxides were prepared by coprecipitation method;
[0016] Layered MoS2 was synthesized by hydrothermal method;
[0017] The obtained lead-aluminum layered double metal hydroxide is mixed with a silane coupling agent and a first solvent to react to obtain an intermediate complex;
[0018] The obtained intermediate complex is mixed with the obtained layered molybdenum disulfide, and the reaction is performed to obtain a composite crystal seed for recovering lead ions in wastewater.
[0019] As a preferred technical solution of the present disclosure, the step of preparing lead-aluminum layered double hydroxide by the co-precipitation method includes: mixing a mixed metal salt solution with an alkaline solution to react to obtain lead-aluminum layered double hydroxide; the mixed metal salt solution includes a soluble lead salt and a soluble aluminum salt.
[0020] Preferably, in the mixed metal salt solution, the concentration of Pb is 4-8 mol / L, for example 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L or 8 mol / L, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0021] Preferably, in the mixed metal salt solution, the concentration of Al is 1.5-5 mol / L, for example 1.5 mol / L, 2 mol / L, 3 mol / L, 4 mol / L or 5 mol / L, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0022] Preferably, the alkaline solution comprises sodium carbonate and / or sodium hydroxide.
[0023] Preferably, in the alkaline solution, the concentration of sodium carbonate is 0.4-1.6 mol / L, for example 0.4 mol / L, 0.6 mol / L, 0.8 mol / L, 1.0 mol / L, 1.2 mol / L, 1.4 mol / L or 1.6 mol / L, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0024] Preferably, in the alkaline solution, the concentration of sodium hydroxide is 1-3.5 mol / L, for example, 1 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L or 3.5 mol / L, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0025] Preferably, the volume ratio of the mixed metal salt solution to the alkaline solution is 1:(1-5), such as 1:1, 1:2, 1:3, 1:4 or 1:5, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0026] Preferably, the reaction temperature of the co-precipitation method for preparing lead aluminum layered double hydroxide is 30-60°C, such as 30°C, 40°C, 50°C or 60°C, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0027] Preferably, the reaction time for preparing lead aluminum layered double hydroxide by the coprecipitation method is 30-120 min, such as 30 min, 60 min, 90 min or 120 min, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0028] Preferably, the obtained lead aluminum layered double hydroxide needs to be dried.
[0029] Preferably, the drying temperature is 30-40°C, such as 30°C, 32°C, 36°C or 40°C, but is not limited to the listed values, and other values not listed within the range are also applicable.
[0030] Preferably, the drying time is 6-12 h, such as 6 h, 8 h, 10 h or 12 h, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0031] As a preferred technical solution of the present disclosure, the step of synthesizing layered molybdenum disulfide by the hydrothermal method includes: mixing a molybdenum source and a sulfur source with a second solvent according to a stoichiometric ratio, and vacuum drying the precipitate obtained after the reaction to obtain layered molybdenum disulfide.
[0032] Preferably, the molybdenum source comprises ammonium molybdate.
[0033] Preferably, the sulfur source comprises thiourea and / or sodium thiosulfate.
[0034] Preferably, the second solvent comprises water.
[0035] Preferably, the reaction temperature for the hydrothermal synthesis of layered molybdenum disulfide is 150-170°C, such as 150°C, 155°C, 160°C, 165°C or 170°C, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0036] Preferably, the reaction time for the hydrothermal synthesis of layered molybdenum disulfide is 8-10 h, such as 8 h, 8.5 h, 9 h or 10 h, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0037] Preferably, the hydrothermal synthesis of layered molybdenum disulfide is carried out under a protective atmosphere.
[0038] Preferably, the reaction pressure of the hydrothermal synthesis of layered molybdenum disulfide is 0.02-0.3 GPa, for example, 0.02 GPa, 0.05 GPa, 0.1 GPa, 0.15 GPa, 0.2 GPa, 0.25 GPa or 0.3 GPa, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0039] Preferably, the vacuum drying temperature is 50-80°C, such as 50°C, 60°C, 70°C or 80°C, but is not limited to the listed values, and other values not listed within the range are also applicable.
[0040] As a preferred technical solution of the present disclosure, the silane coupling agent includes one or more of vinyl triethoxysilane, vinyl trimethoxysilane or vinyl tri(β-methoxyethoxy)silane, such as a combination of vinyl triethoxysilane and vinyl trimethoxysilane, a combination of vinyl trimethoxysilane and vinyl tri(β-methoxyethoxy)silane, etc.
[0041] Preferably, the first solvent comprises water.
[0042] Preferably, the mass ratio of the lead aluminum layered double hydroxide to the silane coupling agent is 1:(0.04-0.4), for example, 1:0.04, 1:0.08, 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35 or 1:0.4, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0043] Preferably, the reaction time of the lead aluminum layered double hydroxide and the silane coupling agent is 3-12h, for example 3h, 4h, 5h, 6h, 8h, 10h or 12h, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0044] Preferably, the reaction temperature of the lead aluminum layered double hydroxide and the silane coupling agent is 10-45°C, such as 10°C, 20°C, 30°C, 40°C or 45°C, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0045] As a preferred technical solution of the present disclosure, the mass ratio of the intermediate complex to the molybdenum disulfide is 1:(0.1-0.6), for example, 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5 or 1:0.6, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0046] Preferably, the reaction temperature of the intermediate complex and the molybdenum disulfide is 25-55°C, such as 25°C, 30°C, 35°C, 40°C, 45°C or 55°C, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0047] Preferably, the reaction time of the intermediate complex and the molybdenum disulfide is 30-150 min, for example, 30 min, 60 min, 90 min, 120 min or 150 min, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0048] In a third aspect, the present disclosure provides a nuclear crystal granulation and salt separation process, in which the composite crystal seed as described in the first aspect or the composite crystal seed prepared by the preparation method as described in the second aspect is used to treat lead-containing wastewater;
[0049] Preferably, the metal ions in the lead-containing wastewater also include one or more of cobalt, zinc, cadmium or nickel.
[0050] As a preferred technical solution of the present disclosure, the nuclear crystal granulation and salt separation process comprises the following steps:
[0051] (1) filling the composite seed crystal into a nuclear crystal granulation reactor;
[0052] (2) introducing the lead-containing wastewater and the precipitant into a nuclear crystal granulation reactor respectively, so that the seed crystals are fluidized and react;
[0053] The regenerated water obtained after the reaction flows out from the upper end of the nuclear crystal granulation reactor, and the granulated body obtained after the reaction is discharged from the lower end of the nuclear crystal granulation reactor.
[0054] Preferably, the filling height of the composite seed crystals in step (1) is 15-25% of the height of the nuclear crystal granulation reactor, such as 15%, 20% or 25%, etc., but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0055] Preferably, the precipitant in step (2) comprises sodium carbonate solution and / or sodium hydroxide solution.
[0056] Preferably, the ratio of the concentration of the precipitant in step (2) to the concentration of lead ions in the lead-containing wastewater is (0.4-0.8):1, such as 0.4:1, 0.5:1, 0.6:1, 0.7:1 or 0.8:1, but is not limited to the listed values, and other unlisted values within the range are also applicable, wherein the unit of concentration is mg / L.
[0057] Preferably, the flow rate ratio of the precipitant to the flow rate of the lead-containing wastewater is 1:(15-20), for example 1:15, 1:16, 1:17, 1:18, 1:19 or 1:20, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable, wherein the unit of flow rate is L / h.
[0058] Preferably, the reaction time in step (2) is 1-10 min, for example, 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min or 10 min, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0059] In the present disclosure, the flow rate of lead-containing wastewater, the concentration of the precipitant and the inlet flow rate can be selected and adjusted by those skilled in the art according to hydraulic and water chemical conditions.
[0060] Compared with the prior art, the technical solution provided by the embodiments of the present disclosure has the following advantages:
[0061] The present invention uses lead-aluminum layered double metal hydroxide as a matrix material, and obtains lead-specific composite seeds by loading layered molybdenum disulfide on its surface. The composite seeds enhance the selective capture / enrichment capability of lead ions in new energy battery wastewater, significantly improve the purity and density of the granules, and the obtained granules have a low moisture content and can be directly put into industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present disclosure and, together with the description, serve to explain the principles of the present disclosure.
[0063] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0064] Figure 1 FT-IR comparison chart of the composite seed crystals obtained in Examples 1-3 of the present disclosure and the seed crystals obtained in Comparative Examples 2-3.
[0065] Figure 2 It is an XRD comparison diagram of the composite seed crystals obtained in Examples 1-3 of the present disclosure and the seed crystals obtained in Comparative Examples 2-3.
[0066] Figure 3 This is a comparison chart of the removal rates of cobalt ions, nickel ions, lead ions and zinc ions in multi-component lead-containing wastewater by the composite crystal seeds obtained in Examples 1-3 of the present disclosure and the crystal seeds obtained in Comparative Examples 2-3.
[0067] Figure 4 This is a comparison chart of the removal rates of cobalt ions, nickel ions, lead ions and zinc ions in multi-element lead-containing wastewater using the five commercial crystal seeds described in Comparative Example 1 of the present disclosure. DETAILED DESCRIPTION
[0068] In order to more clearly understand the above-mentioned objectives, features and advantages of the present disclosure, the scheme of the present disclosure will be further described below. It should be noted that the embodiments of the present disclosure and the features in the embodiments can be combined with each other without conflict.
[0069] In the following description, many specific details are set forth to facilitate a full understanding of the present disclosure, but the present disclosure may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present disclosure, rather than all of the embodiments.
[0070] Example 1
[0071] This embodiment provides a composite crystal seed for recovering lead ions in wastewater and a preparation method thereof, wherein the composite crystal seed comprises a lead-aluminum layered double metal hydroxide and a layered molybdenum disulfide supported on the surface of the lead-aluminum layered double metal hydroxide;
[0072] The mass ratio of the lead aluminum layered double hydroxide to the layered molybdenum disulfide is 1:0.6;
[0073] In the lead-aluminum layered double hydroxide, the molar ratio of lead to aluminum is 4:1.5.
[0074] The preparation method comprises the following steps:
[0075] Preparation of lead-aluminum layered double hydroxide by coprecipitation method:
[0076] An alkaline solution is prepared, including sodium carbonate and sodium hydroxide, wherein the concentration of sodium carbonate is 0.4 mol / L and the concentration of sodium hydroxide is 1 mol / L;
[0077] A mixed metal salt solution is prepared, including lead chloride and aluminum chloride, wherein the concentration of the lead chloride is 4 mol / L and the concentration of the aluminum chloride is 1.5 mol / L;
[0078] The mixed metal salt solution and the alkaline solution were mixed in a volume ratio of 1:1, reacted at 30°C for 30 minutes, and the obtained precipitate was dried at 30°C for 6 hours after solid-liquid separation to obtain lead-aluminum layered double hydroxide, denoted as Pb-Al-LDH.
[0079] Hydrothermal synthesis of layered molybdenum disulfide:
[0080] Dissolve 2mmol of ammonium molybdate tetrahydrate in 60ml of deionized water, stir for 10min, then add 4mmol of thiourea and continue stirring for 45min to obtain a clear and transparent solution; transfer the obtained clear and transparent solution to a 100ml NSC classic fast-opening magnetic stirring reactor. After sealing, introduce nitrogen and react at 100MPa and 160℃ for 8h to obtain a black precipitate. The obtained black precipitate is washed with deionized water and ethanol in turn, and then dried at 60℃ under vacuum for 10h to obtain layered molybdenum disulfide, recorded as MoS2.
[0081] 1 g of the obtained lead aluminum layered double hydroxide and 0.04 g of vinyltriethoxysilane were added to 50 mL of water, heated in a water bath at 10°C, and reacted for 3 hours to obtain an intermediate complex; then 0.6 g of layered molybdenum disulfide was added thereto, heated in a water bath at 25°C, and reacted for 30 minutes to obtain a composite seed crystal, recorded as (Pb-Al-LDH)-MoS2(0.6), where 0.6 represents the mass ratio of MoS2 to Pb-Al-LDH.
[0082] Example 2
[0083] The present embodiment provides a method for preparing a composite crystal seed for recovering lead ions in wastewater. The preparation method refers to the preparation method in Example 1, with the only difference being that: 1 g of the obtained lead aluminum layered double hydroxide and 0.22 g of vinyl triethoxysilane are added to 50 mL of water, heated in a water bath at 20°C, and reacted for 6 hours to obtain an intermediate complex; then 0.3 g of layered molybdenum disulfide is added thereto, heated in a water bath at 45°C, and reacted for 75 minutes to obtain a composite crystal seed, recorded as (Pb-Al-LDH)-MoS2(0.3).
[0084] Example 3
[0085] The present embodiment provides a method for preparing a composite crystal seed for recovering lead ions in wastewater. The preparation method refers to the preparation method in Example 1, with the only difference being that: 1 g of the obtained lead aluminum layered double hydroxide and 0.4 g of vinyl tri(β-methoxyethoxy)silane are added to 50 mL of water, heated in a water bath at 45°C, and reacted for 12 hours to obtain an intermediate complex; then 0.15 g of layered molybdenum disulfide is added thereto, heated in a water bath at 55°C, and reacted for 150 minutes to obtain a composite crystal seed, recorded as (Pb-Al-LDH)-MoS2(0.15).
[0086] Comparative Example 1
[0087] This comparative example provides 5 commercial seed crystals, including:
[0088] The first commercial seed crystal, quartz sand;
[0089] The second commercial seed crystal, garnet;
[0090] The third commercial seed, coal gangue;
[0091] The fourth commercial seed, hematite;
[0092] The fifth commercial crystal seed is fluorite.
[0093] Comparative Example 2
[0094] This comparative example provides a seed crystal, which is a lead-aluminum layered double metal hydroxide, prepared by referring to the preparation method in Example 1.
[0095] Comparative Example 3
[0096] This comparative example provides a seed crystal, which is layered molybdenum disulfide and is prepared by referring to the preparation method in Example 1.
[0097] The composite seed crystals obtained in Examples 1-3 and the seed crystals obtained in Comparative Examples 2-3 were characterized.
[0098] Among them, the FT-IR comparison diagram of the composite seed obtained in Example 1 ((Pb-Al-LDH)-MoS2(0.6)), the composite seed obtained in Example 2 ((Pb-Al-LDH)-MoS2(0.3)), the composite seed obtained in Example 3 ((Pb-Al-LDH)-MoS2(0.15)), the seed obtained in Comparative Example 2 (Pb-Al-LDH) and the seed obtained in Comparative Example 3 (MoS2) is as shown in FIG. Figure 1 As shown. Figure 1 It can be seen that Pb-Al-LDH, (Pb-Al-LDH)-MoS2(0.6), (Pb-Al-LDH)-MoS2(0.3) and (Pb-Al-LDH)-MoS2(0.15) at 682cm -1 、1407cm -1 and 1738cm -1 There are characteristic peaks at 1641cm -1 、1046cm -1 There are obvious characteristic peaks appearing at the corresponding peak positions in the corresponding composite seeds, which indicates that MoS2 has been successfully loaded on the surface of the Pb-A-LDH matrix material.
[0099] The XRD comparison diagrams of the composite seed crystal obtained in Example 1 ((Pb-Al-LDH)-MoS2(0.6)), the composite seed crystal obtained in Example 2 ((Pb-Al-LDH)-MoS2(0.3)), the composite seed crystal obtained in Example 3 ((Pb-Al-LDH)-MoS2(0.15)), the seed crystal obtained in Comparative Example 2 (Pb-Al-LDH) and the seed crystal obtained in Comparative Example 3 (MoS2) are shown in FIG. Figure 2 As shown. Figure 2 It can be seen that the characteristic peaks of (Pb-Al-LDH)-MoS2(0.6), (Pb-Al-LDH)-MoS2(0.3) and (Pb-Al-LDH)-MoS2(0.15) at 14.5°, 39.7° and 60.5° correspond to the characteristic peaks of MoS2, respectively, while Pb-Al-LDH does not have corresponding characteristic peaks at the above positions; for Pb-Al-LDH, its characteristic peaks at 24.7°, 26.9° and 34.3° indicate that the synthesis of Pb-Al-LDH is successful, and the corresponding characteristic peaks also appear at the above positions for the above three different proportions of composite seeds, which all indicate that MoS2 has been successfully loaded on the surface of Pb-Al-LDH, which is mutually confirmed by the infrared spectrum.
[0100] Performance Test:
[0101] The composite crystal seeds obtained in Examples 1-3, the five commercial crystal seeds described in Comparative Example 1, and the crystal seeds described in Comparative Examples 2-3 were used as the crystal seeds to be tested, and the lead-containing wastewater was treated by the nuclear crystal granulation and salt separation process. The specific process includes:
[0102] S1: filling the seed crystals to be tested into the 2 m high nuclear crystal granulation reactor respectively and independently, and the filling height is 20% of the height of the nuclear crystal granulation reactor;
[0103] S2: Lead-containing wastewater is introduced from the bottom of the nuclear crystal granulation reactor at a flow rate of 20 L / h. At the same time, a sodium carbonate solution with a concentration of 124 mg / L is introduced from the lower end of the side wall of the nuclear crystal granulation reactor at a flow rate of 1.2 L / h to make the seed crystals to be tested fluidized and react. The reaction time is 10 min.
[0104] The regenerated water obtained after the reaction flows out from the water outlet of the nuclear crystal granulation reactor, and the granulated body obtained after the reaction is discharged from the granulated body discharge port of the nuclear crystal granulation reactor.
[0105] Among them, the specific composition of lead-containing wastewater is shown in Table 1.
[0106] Table 1
[0107] Lead ions Cobalt ion Nickel Ion Zinc ion Ion concentration (mg / L) 207.2 58.93 58.69 65.41
[0108] The concentration and turbidity of the four ions in the reclaimed water were measured, and the results are shown in Table 2; the removal rates of the four ions in the reclaimed water were calculated, as shown in Table 3.
[0109] Table 2
[0110]
[0111] Table 3
[0112]
[0113]
[0114] In addition, the removal rates of cobalt ions, nickel ions, lead ions and zinc ions in multi-element lead-containing wastewater by the composite seed crystal obtained in Example 1 ((Pb-Al-LDH)-MoS2(0.6)), the composite seed crystal obtained in Example 2 ((Pb-Al-LDH)-MoS2(0.3)), the composite seed crystal obtained in Example 3 ((Pb-Al-LDH)-MoS2(0.15)), the seed crystal obtained in Comparative Example 2 (Pb-Al-LDH) and the seed crystal obtained in Comparative Example 3 (MoS2) are shown in the following figure: Figure 3 As shown. Figure 3It can be seen that compared with Pb-Al-LDH material and MoS2 material, the composite seed crystal disclosed in the present invention has better selective separation and removal ability, and the removal rate of lead ions can reach more than 95.9%, while the removal rates of the other three ions are all less than 20%.
[0115] The comparison of the removal rates of cobalt ions, nickel ions, lead ions and zinc ions by the five commercial crystal seeds described in Comparative Example 1 in multi-element lead-containing wastewater is shown in the figure below: Figure 4 As shown. Figure 4 It can be seen that the five commercial crystal seeds have good removal capabilities for cobalt ions, lead ions, zinc ions, and nickel ions in multi-element lead-containing wastewater. Among them, compared with other metal ions, the five commercial crystal seeds have a higher removal rate for lead ions, but compared with the removal rates of the other three ions, the maximum difference does not exceed 30%, which shows that the five commercial crystal seeds have weak selective recovery capabilities for lead ions, which are not enough to classify and recover them with the other three metal ions, resulting in low purity of the final granules and low recovery efficiency.
[0116] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0117] The above description is only a specific embodiment of the present disclosure, so that those skilled in the art can understand or implement the present disclosure. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present disclosure. Therefore, the present disclosure will not be limited to the embodiments described herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A composite seed crystal for recovering lead ions in wastewater, characterized in that: The composite seed crystal includes a lead-aluminum layered double metal hydroxide and a layered molybdenum disulfide supported on the surface of the lead-aluminum layered double metal hydroxide.
2. The composite seed crystal according to claim 1, characterized in that In the composite seed crystal, the mass ratio of the lead aluminum layered double hydroxide to the layered molybdenum disulfide is 1:(0.15-0.6).
3. The composite seed crystal according to claim 1 or 2, characterized in that: In the lead-aluminum layered double hydroxide, the molar ratio of lead to aluminum is (4-8):(1.5-5).
4. A method for preparing a composite seed crystal according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: Lead-aluminum layered double hydroxides were prepared by coprecipitation method; Layered MoS2 was synthesized by hydrothermal method; The obtained lead-aluminum layered double metal hydroxide is mixed with a silane coupling agent and a first solvent to react to obtain an intermediate complex; The obtained intermediate complex is mixed with the obtained layered molybdenum disulfide, and the reaction is performed to obtain a composite crystal seed for recovering lead ions in wastewater.
5. The preparation method according to claim 4, characterized in that: The steps of preparing the lead-aluminum layered double metal hydroxide by the coprecipitation method include: mixing a mixed metal salt solution with an alkaline solution to react and obtain the lead-aluminum layered double metal hydroxide; the mixed metal salt solution includes a soluble lead salt and a soluble aluminum salt; Preferably, in the mixed metal salt solution, the concentration of Pb is 4-8 mol / L; Preferably, in the mixed metal salt solution, the concentration of Al is 1.5-5 mol / L; Preferably, the alkaline solution includes sodium carbonate and / or sodium hydroxide; Preferably, in the alkaline solution, the concentration of sodium carbonate is 0.4-1.6 mol / L; Preferably, in the alkaline solution, the concentration of sodium hydroxide is 1-3.5 mol / L; Preferably, the volume ratio of the mixed metal salt solution to the alkaline solution is 1:(1-5); Preferably, the reaction temperature for preparing the lead-aluminum layered double hydroxide by the coprecipitation method is 30-60°C; Preferably, the reaction time for preparing the lead-aluminum layered double hydroxide by the co-precipitation method is 30-120 min.
6. The preparation method according to claim 4 or 5, characterized in that: The step of synthesizing layered molybdenum disulfide by the hydrothermal method comprises: mixing a molybdenum source and a sulfur source with a second solvent according to a stoichiometric ratio, and vacuum drying a precipitate obtained after the reaction to obtain layered molybdenum disulfide; Preferably, the molybdenum source comprises ammonium molybdate; Preferably, the sulfur source comprises thiourea and / or sodium thiosulfate; Preferably, the second solvent comprises water; Preferably, the reaction temperature for synthesizing layered molybdenum disulfide by the hydrothermal method is 150-170°C; Preferably, the reaction time of the hydrothermal method for synthesizing layered molybdenum disulfide is 8-10h; Preferably, the hydrothermal synthesis of layered molybdenum disulfide is carried out under a protective atmosphere; Preferably, the reaction pressure of the hydrothermal method for synthesizing layered molybdenum disulfide is 0.02-3 GPa; Preferably, the vacuum drying temperature is 50-80°C.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The silane coupling agent includes one or more of vinyl triethoxy silane, vinyl trimethoxy silane or vinyl tri (β-methoxyethoxy) silane; Preferably, the first solvent comprises water; Preferably, the mass ratio of the lead aluminum layered double hydroxide to the silane coupling agent is 1:(0.04-0.4); Preferably, the reaction time of the lead aluminum layered double hydroxide and the silane coupling agent is 3-12 hours; Preferably, the reaction temperature of the lead aluminum layered double hydroxide and the silane coupling agent is 10-45°C.
8. The preparation method according to any one of claims 4 to 7, characterized in that: The mass ratio of the intermediate complex to the molybdenum disulfide is 1:(0.1-0.6); Preferably, the reaction temperature of the intermediate complex and the molybdenum disulfide is 25-55°C; Preferably, the reaction time of the intermediate complex and the molybdenum disulfide is 30-150 min.
9. A nuclear crystal granulation and salt separation process, characterized in that: In the nuclear crystal granulation and salt separation process, the lead-containing wastewater is treated by using the composite crystal seeds as described in claims 1-3 or the composite crystal seeds prepared by the preparation method as described in any one of claims 4-8; Preferably, the metal ions in the lead-containing wastewater also include one or more of cobalt, zinc, cadmium or nickel.
10. The nuclear crystal granulation and salt separation process according to claim 9, characterized in that: The nuclear crystal granulation and salt separation process comprises the following steps: (1) filling the composite seed crystal into a nuclear crystal granulation reactor; (2) introducing the lead-containing wastewater and the precipitant into a nuclear crystal granulation reactor respectively, so that the composite seed crystals are fluidized and react; The regenerated water obtained after the reaction flows out from the upper end of the nuclear crystal granulation reactor, and the granulated body obtained after the reaction is discharged from the lower end of the nuclear crystal granulation reactor; Preferably, the filling height of the composite seed crystals in step (1) is 15-25% of the height of the nuclear crystal granulation reactor; Preferably, the precipitant in step (2) comprises sodium carbonate solution and / or sodium hydroxide solution; Preferably, the ratio of the concentration of the precipitant in step (2) to the concentration of lead ions in the lead-containing wastewater is (0.4-0.8):1, wherein the unit of concentration is mg / L; Preferably, the flow rate ratio of the precipitant to the lead-containing wastewater is 1:(15-20), wherein the unit of flow rate is L / h; Preferably, the reaction time in step (2) is 1-10 min.
Citation Information
Patent Citations
Method for synthesizing molybdenum disulfide single-layer nanometer sheets by space limited range method
CN108394935A
Layered double-metal hydroxide complex for adsorbing heavy metal ions and preparation method and application thereof
CN113413864A
Preparation method of layered double-metal hydroxide based on waste incineration fly ash
CN116903015A
Two-dimensional molybdenum disulfide nano material and preparation method and application thereof
CN118084059A
Continuous flow salt separation treatment system and method and application thereof
CN118724231A